High average power super-continuum generation using 1 [micro sign]m noise burst and highly-nonlinear photonic crystal fibre - Chow, Kin Kee (2013)
Super-continuum generation at 1 mm using amplified spontaneous emission noise burst instead of coherent ultra-short pulses is proposed and demonstrated. The noise burst is generated from pumping an ytterbium-doped fibre followed by external modulation. By launching the amplified noise burst into a highly-nonlinear photonic crystal fibre with dispersion zero at around 1 mm, depolarised super-continuum is generated over 500 nm with a 23 dBm average power.